Software products that develop the personal competence of the student based on the training of the practical software package course - Умиров Бобоёр Бахтиёр ўғли (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article describes the theoretical foundations of the development of personal competence of students through the programs of the application package. A platform for developing students' personal competence has been developed and its importance and terms of use have been shown.